Implementation of ethereum blockchain on transaction recording of white sugar supply chain data - Ratna Ekawati; Yandra Arkeman; Suprihatin Suprihatin; Titi Candra Sunarti (Indonesian Journal of Electrical Engineering and Computer Science, 2023)
The complex supply chain system for the sugar agroindustry supply chain involves many actors, resulting in the asymmetry of information data. It still leads to a lack of data transparency. In the past, data traceability could not be made efficient at every stage, so the record data transaction was not real-time, less accurate, and inefficient coordination between actors. Blockchain is one of the technologies in the 4.0 era as a distributed ledger technology. It can be transparency, traceability, security, immutability, and decentralization. This study aims to design a white sugar agroindustry system based on blockchain technology using the SDLC waterfall stage public. Ethereum is a proof-of-work convention based on the Ropsten test-net on the Metamask wallet. The sugar supply chain system that has been successfully developed allows consumers to track the purchased sugar products based on the transaction hash code sent by the seller. The data listed is the location of the plantation, the quantity (quintal) and quality of sugarcane (percentage), and the purchase price. A web-based blockchain application could be used as a model by national sugar factories to help them make enough sugar food for themselves.